1988
DOI: 10.1177/1077727x8801600303
|View full text |Cite
|
Sign up to set email alerts
|

Fashion Opinion Leadership and Media Exposure among College Women in India

Abstract: The concept of fashion leadership among college women in India was examined by assessing the attention given to media exposure (fashion information sources) of identified opinion leaders and fashion nonleaders. A survey design with a pre tested questionnaire was used to conduct the research. The final sample con sisted of 509 college women from four universities in northwestern India. Anal ysis of variance and chi square analysis were used to test the hypotheses. The findings revealed that fashion opinion lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In comparison with previous studies (Painter and Granzin 1976;Polegato and Wall 1980;Chowdhary and Dicky 1988; Goldsmith et αl. 1991;Workman and Johnson 1993;Goldsmith et al 1996), the distribution of fashion groups was different in Hong Kong.…”
Section: The Distribution Of Various Fashion Groups Among Young Hong mentioning
confidence: 54%
See 4 more Smart Citations
“…In comparison with previous studies (Painter and Granzin 1976;Polegato and Wall 1980;Chowdhary and Dicky 1988; Goldsmith et αl. 1991;Workman and Johnson 1993;Goldsmith et al 1996), the distribution of fashion groups was different in Hong Kong.…”
Section: The Distribution Of Various Fashion Groups Among Young Hong mentioning
confidence: 54%
“…Marketer-dominated sources were important to fashion leaders, but consumer-dominated sources were important for fashion followers. In addition, Painter and Granzin (1976) and Chowdhary and Dicky (1988) further investigated fashion leaders from the viewpoint of gender. Painter and Granzin reported that male fashion innovators tended to be young, mobile, have few children, and have a higher education level than non-innovators.…”
Section: Fashion Opinion Leadershipmentioning
confidence: 98%
See 3 more Smart Citations